Microstructure and thermal analysis of lithium ferrite pre-milled in a high-energy ball mill; Journal of Thermal Analysis and Calorimetry; Vol. 134, iss. 1 - Lysenko E. N. Elena Nikolaevna; Malyshev A. V. Andrei Vladimirovich; Vlasov V. A. Vitaliy Anatolievich; Nikolaev E. V. Evgeny Vladimirovich; Surzhikov A. P. Anatoly Petrovich (2018, 2018)
Title screen